IN THE SYSTEM OF MYTHOLOGY OF ENGLISH AND UZBEK FAIRY TALES THE PLACE OF SPELLONYM (Spectrum Journal of Innovation, Reforms and Development, 2023)
In this article, Uzbek and English folk tales they have different and similar aspects to each other. Besides that, the opinions of several scientists about the differences have also found their example. This article reflects the differences and similarities of Uzbek and English folktales. In addition, the opinions of several scientists about these differences have also found their example.[1]